EFFECTIVNESS OF USING INDUCTIVE AND DEDUCTIVE APPROACH OF TEACHING ENGLISH FOR SHCOOL AND UNIVERSITY STUDENTS - Dauletmuratova, M.Y. (SCIENCE and SOCIETY, 2023)
The study investigates the comparative effectiveness of teaching English grammar by using deductive and inductive teaching models. The study also attempts to see which of these two methods has a positive effect on the grammar academic achievement of the university students and elementary school students in Uzbekistan so it answers the following questions:• What is the effect of inductive method on grammar achievement compared with deductive method at university level?• What is the effect of inductive method on grammar achievement compared with deductive method at elementary stage?To answer the questions of the study, the researcher prepares two programs based on inductive and deductive methods for each level based on its syllabus.The sample consists 180 students; eighty at the 1st year level in English departments at university level and one hundred at the elementary stage. The participants of the study consisted of four assigned sections.